Michel Foucault : el suicidio del autor - Colacrai, Pablo (UNR Editora, 2005)
El artículo comienza trazando un paralelo entre el cuento de Borges, “Pierre Menard, autor del Quijote”, y la posición que adopta Michel Foucault en torno a la problemática del autor. Se intenta ejemplificar, a través de la ficción y la exageración propias del cuento, las consecuencias que puede acarrear leer la obra a través del nombre de su autor. Luego, se demuestra la importancia de esta distinción dentro del pensamiento Foucaultiano. El autor es una construcción, así como la obra y el texto, y dentro de una metodología (arqueología) que intenta colegir sistemas de pensamiento, posibilidad de aparición de enunciados, en fin, episteme; enarbolar la figura del autor no hace más que entorpecer y obstaculizar la tarea.

The article draws a parallel between Borges´s work “Pierre Menard, autor del Quijote”, and Michel Foucault´s theoretical discussion about the issue of the author. The idea is to illustrate through fiction and the literary exaggeration of this particular story, the consequences of reading a work on behalf of its author. Then, the article shows the importance of this subject has in Michel Foucault´s thought. Both, the author and the work as well as the text itself, constitute a construction within a methodology (archaeology) which intends to grasp systems or ways of thinking, the possibility for certain enunciations to emerge, that is to say the episteme. In this sense, emphasizing the figure of the author is considered not only misleading but also an obstacle to this task.
Keywords: muerte del autor; episteme; enunciados; obra; texto; discurso; author’s death; statements; work; text; discourse